2010
DOI: 10.1515/hf.2010.061
|View full text |Cite
|
Sign up to set email alerts
|

Water sorption in wood and modified wood at high values of relative humidity. Part 2: Appendix. Theoretical assessment of the amount of capillary water in wood microvoids

Abstract: A theoretical study of the amount of moisture held in wood as capillary condensed water in the relative humidity (RH) range of 90-99.9% is carried out. The study is based on idealized geometries of the softwood structure related to micrographs. It is confined to structural elements such as bordered pits and the pointed ends of tracheids. The theoretical amount of water in these elements is found by employing the Kelvin equation. An equal amount of earlywood and latewood cells with different geometries and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 7 publications
3
20
0
1
Order By: Relevance
“…These methods yield FSP values in the 38.5-42.5 % MC range for different softwood species. There is thus a difference of about 10 % moisture between the FSP around 30 % MC which is obtained if a change in how strongly a physical property of wood (electrical conductivity, shrinkage, strength properties) depends on the moisture content is used as basis for the definition (Stamm 1929(Stamm , 1971) and the FSP of about 40 % MC which is obtained if based on the amount of water present in the cell wall at equilibrium conditions close to 100 % RH (Hernández and Bizoň 1994;Hill et al 2005;Engelund et al 2010;Thygesen et al 2010;Hoffmeyer et al 2011). This discrepancy raises the question why the last 10 % MC within the cell wall (i.e., from 30 to 40 % MC) do not affect the physical properties of the cell wall as much as the first 30 % MC, while still apparently being present as bound water Thygesen et al 2010;Hoffmeyer et al 2011).…”
Section: Green Wood and Fibre Saturationmentioning
confidence: 99%
“…These methods yield FSP values in the 38.5-42.5 % MC range for different softwood species. There is thus a difference of about 10 % moisture between the FSP around 30 % MC which is obtained if a change in how strongly a physical property of wood (electrical conductivity, shrinkage, strength properties) depends on the moisture content is used as basis for the definition (Stamm 1929(Stamm , 1971) and the FSP of about 40 % MC which is obtained if based on the amount of water present in the cell wall at equilibrium conditions close to 100 % RH (Hernández and Bizoň 1994;Hill et al 2005;Engelund et al 2010;Thygesen et al 2010;Hoffmeyer et al 2011). This discrepancy raises the question why the last 10 % MC within the cell wall (i.e., from 30 to 40 % MC) do not affect the physical properties of the cell wall as much as the first 30 % MC, while still apparently being present as bound water Thygesen et al 2010;Hoffmeyer et al 2011).…”
Section: Green Wood and Fibre Saturationmentioning
confidence: 99%
“…For instance, Engelund et al (2010) found that even at a relative humidity of 99.9%, samples of wood took up only about 0.35% of capillary condensed water in comparison to the dry mass of the wood. Likewise, Thygesen et al (2010) found that capillary condensation does not play a significant role in water sorption by wood in the relative humidity range up to 99.9%.…”
Section: Localized and Limited Nature Of Capillary Condensationmentioning
confidence: 99%
“…This is due to potential changes after modification in the contact angle between wood surface and wetting liquid. Such change will affect EMC in the over-hygroscopic range as predicted by Engelund et al (2010). The contact angle of liquids with modified wood has been investigated in several studies by the Wilhelmy and sessile drop methods.…”
Section: Pressure Plate Techniquementioning
confidence: 99%